Manajemen Pendidikan Anak Usia Dini (Studi Pada Tk Negeri Pembina Kecamatan Mandau Kabupaten Bengkalis) - Nova Wahyuni; Suarni Norawati; Abshor Marantika (Ranah Research : Journal of Multidisciplinary Research and Development, 2023)
The purpose of this research is to determine the Management of Early Childhood Education in the Pembina State Kindergarten, Mandau District. This research uses descriptive qualitative methods. The results of this research found that planning was prepared through work meetings by planning (1) Annual and Semester Planning (2) Semester Program (3) Weekly Activity Planning (3) Daily Activity Planning. Implementation of learning in the Pembina State Kindergarten, Mandau District, is generally the same as other PAUD or Kindergarten, including: (1) Preparation/arrangement of materials and play equipment/APE (Educative play equipment). (2) Welcoming Children's Attendance (3) Daily Activity Facilities (4) Opening Activities (5) Transitions (6) Praying Together (6) Group Activities (7) Eating Together (8) Closing Activities. The evaluation carried out was divided into 2 stages, namely: internal evaluation carried out by meetings with school principals and teachers and the second evaluation was an evaluation meeting carried out by the Education Office.